DESKRIPSI KITAB SENJATA MUKMIN DAN RISALAH DOA - Yulizar, Muhammad Adriani; Ilhami, Hamidi (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
This article describes the work of K.H. Husin Qadri and K.H. Jafar Sabran; twoproductive scholarswho wrote manyreligious literatures related to monotheism, sharia, morals, deedsand prayers. Â K.H. Husin Kadri,a famous writer in his time, had Â a brilliant idea to writeÂ a book contained ofÂ collection of prayers al-MasturatÂ from Al-Quran and Hadith.Â Althoughhe did not include the references of Â prayers and quotation used in his book,Â the Book ofSenjata Mukmin was devotedto students community and Martapura residentsÂ who have understood, and memorizedthe verses or hadith Â in that book.Â K.H. Husin Kadri Â also includedÂ a material of monotheismÂ which described the explanation of Â twentycharacteristics. Â The Book of Risalah Doawas composedwithmodel and format designed by the editors to make it different from other peoples work, accompanied by interesting information quoted from credible sources. This book was completed withnumber of verses and chapters, the source of hadithâsquotations and sayings Â of scholarsfrom other books.